Strategi Pengembangan UMKM Dengan Tren Digitalisasi di Desa Kutopohaci Kabupaten Karawang - Irmawati, Luki; Putri, Nadhila; Pertiwi Hari Sandi, Santi; Epty Hidayaty, Dwi (Rifa'Institute, 2023)
This study aims to gain a deeper understanding of the digital marketing strategies employed by K-Beat-A Dimsum. A qualitative approach is utilized, with a focus on the individual as the unit of analysis, specifically the owner of K-Beat-A Dimsum. The research method employed is descriptive, involving in-depth interviews with the owner of K-Beat-A Dimsum, as well as observations and literature review. The findings of this study are expected to provide insights into the efforts that K-Beat-A Dimsum can undertake to leverage their strengths, strengthen their position in the market, and overcome existing challenges. By enhancing their digital marketing strategies, optimizing collaborations with online food delivery platforms, and actively engaging with customers, K-Beat-A Dimsum can improve sales, enhance brand awareness, and expand their market share.